Construction, Operation and Maintenance of Network System(Junior Level) - Huawei Technologies Co., Ltd (Springer Nature, 2023)
This open access book follows the development rules of network technical talents, simultaneously placing its focus on the transfer of network knowledge, the accumulation of network skills, and the improvement of professionalism. Through the complete process from the elaboration of the theories of network technology to the analysis of application scenarios then to the design and implementation of case projects, readers are enabled to accumulate project experience and eventually acquire knowledge and cultivate their ability so as to lay a solid foundation for adapting to their future positions. This book comprises six chapters, which include "General Operation Safety of Network System," "Cabling Project," "Hardware Installation of Network System," "Basic Knowledge of Network System," "Basic Operation of Network System," and "Basic Operation and Maintenance of Network System." This book can be used for teaching and training for the vocational skills certification of network system construction, operation, and maintenance in the pilot work of Huawei's "1+X" Certification System, and it is also suitable as a textbook for application-oriented universities, vocational colleges, and technical colleges. In the meantime, it can also serve as a reference book for technicians engaged in network technology development, network management and maintenance, and network system integration. As the world's leading ICT (information and communications technology) infrastructure and intelligent terminal provider, Huawei Technologies Co., Ltd. has covered many fields such as data communication, security, wireless, storage, cloud computing, intelligent computing, and artificial intelligence. Taking Huawei network equipment (routers, switches, wireless controllers, and wireless access points) as the platform, and based on network engineering projects, this book organizes all the contents according to the actual needs of the industry.